Ballistic and aerodynamic characteristics of the early flight phase determining performance in ski-jumping - Schwameder, H.; Müller, E.; De Monte, G.; Potthast, W.; Brüggemann, G. P.; Virmavirta, M.; Isolehto, J.; Komi, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Most of the studies on kinematics in ski-jumping deal with the take-off and the early flight phase with respect to the performance limiting factors in hill jumps. The take-off is attributed the highest significance in ski-jumping (Arndt et al. 1995, Schwameder & Müller 1995). The early flight phase is another sensitive phase in hill jumps. Two studies ascertain performance-related variables using multivariant approaches. According to the studies by Schwameder & Müller (1995) the jump length correlated highest (R=0.89) with a combination of high vertical release velocity, high knee-angle velocity, great torque during the take-off and a small body-ski angle after 20 m of flight. A study under competitive conditions (Arndt et al. 1995) showed that a combination of a big forward lean of the upper body, the lower-body and the skis after 17 m, along with a big ski and leg opening angle after 17 m of flight correlated most highly with jump length (R=0.92). During competitions the usage of biomechanical methods for analysing performance in ski-jumping is restricted. Consequently, only few biomechanical data are available collected in competitions and they are primarily restricted to kinematics. Studies in high level competitions as Olympic Games, however, yield data from the world`s best ski-jumpers during the top event of the season. Due to the change in the technique and material used new studies are still necessary to learn more about the function of the take-off and early flight in ski-jumping. So the purpose of the study was to determine the kinematic variables related to performance during the Olympic Games` K90 competition. Methods The take-off and early flight phase (approx. 30 m) of all jumpers of the second round in the K90 ski-jumping Olympic Games competition in Salt Lake City 2002 (32 jumpers) were video-taped with three synchronised video cameras (50 Hz). The co-ordinates of calibration points and the points of rotation of the cameras were geodetically measured to provide panning, tilting and zooming of the cameras. This method has been successfully used in previous studies (Schwameder & Müller 1995, Arndt et al. 1995). After filtering the measured data were used to calculate both ballistic and aerodynamic parameters. The data represent velocities as well as body segment and ski angles after one second of flight. 29 jumps could be evaluated and were separated into group A (first half concerning jump length) and group B (second half). To analyse the difference between group A and B with respect to particular variables ANOVA and t-test designs were used. Results After one second of flight the gradient of the flight path in group A is significantly smaller (on average 0.74°) compared with group B. This is caused by the significantly smaller vertical velocity in group A (p < 0.03). The body-flight path angle is 3.4° and the body-ski angle 3.1° smaller in group A compared with the group jumping shorter. For both variables the differences were found to be significant (p < 0.003). No differences have been observed for the horizontal take-off velocity, the body segment angles and the V-angle of the skis. Discussion The results clearly show that a small body-ski angle in combination with a small vertical velocity of the COM after one second of flight are the best predictors for long flights in ski-jumping. Jumpers who can use the aerodynamic forces in a way to keep horizontal speed in combination with a high lift and who can early reach a compact flight position show a tendency to perform long jumps. These results emphasize the findings of previous studies (Schwameder & Müller 1995, Arndt et al. 1995, Virmavirta et al. 2004). The correlations between these variables and the jump lengths show a tendency to be higher on the big hill (K120) (Virmavirta et al. 2004). This indicates that aerodynamic conditions of the jumpers increase with the size of the hill and therefore factors of explosiveness during take-off are more important on smaller hills.